The Budgetary Effects of Medicaid Expansion on Pennsylvania An Expansion on Previous Work - Price, Carter C. (RAND Corporation, 2013)
In the spring of 2013, RAND conducted an analysis assessing the budget effects of the expansion of Medicaid in Pennsylvania under the Affordable Care Act. The analysis was in part based on a specific set of assumptions regarding 1) the application of Pennsylvania's tax code, and 2) expenditures and revenue sources. This addendum examines the sensitivity of those findings to alternative assumptions.